Brassinosteroid Ameliorates Zinc Oxide Nanoparticles-Induced Oxidative Stress by Improving Antioxidant Potential and Redox Homeostasis in Tomato Seedling - Li, Mengqi; Ahammed, Golam J.; Li, Caixia; Bao, Xiao; Yu, Jingquan; Huang, Chunlei; Yin, Hanqin; Zhou, Jie (Frontiers in Plant Science, 2016)
In the last few decades use of metal-based nanoparticles (MNPs) has been increased significantly that eventually contaminating agricultural land and limiting crop production worldwide. Moreover, contamination of food chain with MNPs has appeared as a matter of public concern due to risk of potential health hazard. Brassinosteroid has been shown to play a critical role in alleviating heavy metal stress; however, its function in relieving zinc oxide nanoparticles (ZnO NPs)-induced phytotoxicity remains unknown. In this study, we investigated the potential role of 24-epibrassinolide (BR) in mitigating ZnO NPs-induced toxicity in tomato seedlings. Seedling growth, biomass production, and root activity gradually decreased, but Zn accumulation increased with increasing ZnO NPs concentration (10–100 mg/L) in growth media (½ MS). The augmentation of BR (5 nM) in media significantly ameliorated 50 mg/L ZnO NPs-induced growth inhibition. Visualization of hydrogen peroxide (H2O2), and quantification of H2O2 and malondialdehyde (MDA) in tomato roots confirmed that ZnO NPs induced an oxidative stress. However, combined treatment with BR and ZnO NPs remarkably reduced concentration of H2O2 and MDA as compared with ZnO NPs only treatment, indicating that BR supplementation substantially reduced oxidative stress. Furthermore, the activities of key antioxidant enzymes such as superoxide dismutase (SOD), catalase, ascorbate peroxidase and glutathione reductase were increased by combined treatment of BR and ZnO NPs compared with ZnO NPs only treatment. BR also increased reduced glutathione (GSH), but decreased oxidized glutathione (GSSG)] and thus improved cellular redox homeostasis by increasing GSH:GSSG ratio. The changes in relative transcript abundance of corresponding antioxidant genes such as Cu/Zn SOD, CAT1, GSH1, and GR1 were in accordance with the changes in those antioxidants under different treatments. More importantly, combined application of BR and ZnO NPs significantly decreased Zn content in both shoot and root of tomato seedlings as compared with ZnO NPs alone. Taken together, this study, for the first time, showed that BR could not only improve plant tolerance to ZnO NPs but also reduce the excess zinc content in tomato seedlings. Such a finding may have potential implication in safe vegetable production in the MNPs-polluted areas.